ENCODING BYZANTINE MUSIC NOTATION (ca. 1600-1814) - Bouris, Nick G; Georgaki, Anastasia; Chaldaeakes, Achilleas G (2018)
This paper discusses a new method for encoding Byzantine Music Neumatic Notation (especially the one developed during the ‘transitory’ period 1670-1814). The Notation of this period is characterized by difficulties and peculiarities. The difficult access to Byzantine manuscripts and their deteriorated condition, complicate reading. In addition, our incomplete knowledge of the interpretation of signs impedes the comprehension of the musical text leading in results that are often in dispute. The fact that sign unions are complex enough together with their presence in various places in a composition make electronic transcriptions the ultimate challenge. Moreover, there does not exist a framework for data encoding and analysis. This work presents a proposal for the development of such a model for the old Byzantine Neumatic Notation in Python. The implementation of this project is still at an initial stage, and focuses, mostly, on the efficient digitization of old manuscripts. The system, even though fully functional, has certain limitations. Some signs are missing, and the musical text is created using microphotographies. Future developments of the program will focus on resolving these deficiencies and adding more features to the system.